Kan markfuktighetskartor användas för att hitta skogsmark med hög bonitet? : ett gis-baserat försök med dtw-index och laserskannad övre höjd - Henriksson, Anders (SLU/Dept. of Forest Ecology and Management, 2015)
The depth-to-water-index (DTW-index) is derived from digital elevation models (DEM) to map soil wetness, in terms of distance from soil surface to the ground water table. The aim of this GIS based study was to investigate the existence of a relationship between DTW-index and forest site productivity (SP). The belief of such an assumed relationship was based on knowledge that the ground water level is related to site properties that can either promote or impede tree growth. Data primarily comprised rasters of the Krycklan catchment in northern Sweden and depicted DTW-index and a laser scanned vegetation height. The 100th height percentile of each pixel in the vegetation raster was assumed to mirror the top-height, letting it act as a relative measure of SP within a delineated area of equal stand age. Areas of equal age were delineated by recognition of fresh clear-cuts in a digitized ortophoto from 1963. Influence from disturbing factors was reduced by selecting areas on till soil where Scots Pine (Pinus Sylvestris L.) dominated. The result suggests a weak and likely non-significant relationship between the variables. The lack of compelling evidence for such a relationship is attributed to the methods used and we suggest a repeated study with a more developed study design.